SFTSV infection in rodents and their ectoparasitic chiggers - Xiao-Lan Gu; Wen-Qing Su; Chuan-Min Zhou; Li-Zhu Fang; Ke Zhu; Dong-Qiang Ma; Fa-Chun Jiang; Ze-Min Li; Dan Li; Shu-Hui Duan; Qiu-Ming Peng; Rui Wang; et al. (Public Library of Science (PLoS), 2022)
SFTSV, a tick-borne bunyavirus causing a severe hemorrhagic fever termed as severe fever with thrombocytopenia syndrome (SFTS). To evaluate the potential role of rodents and its ectoparasitic chiggers in the transmission of SFTSV, we collected wild rodents and chiggers on their bodies from a rural area in Qingdao City, Shandong Province, China in September 2020. PCR amplification of the M and L segments of SFTSV showed that 32.3% (10/31) of rodents and 0.2% (1/564) of chiggers (Leptotrombidium deliense) from the rodents were positive to SFTSV. Our results suggested that rodents and chiggers may play an important role in the transmission of SFTSV, although the efficiency of chiggers to transmit SFTSV needs to be further investigated experimentally. Author summary Severe fever with thrombocytopenia syndrome (SFTS), an emerging hemorrhagic fever in Asia, is caused by SFTSV, a tick-borne bunyavirus. In this study, we analyzed the prevalence of SFTSV in rodents and their ectoparasite chigger mites (Leptotrombidium delicense) with RT-PCR. RT-PCR results showed that one third (32.3%, 10/31) rodents and one chigger (0.2%, 1/564) was positive to SFTSV. Our study suggested that rodents and chiggers may play an important role in the ecology of SFTSV.